Effects of genetics and sex on adolescent behaviors following neonatal ethanol exposure in BXD recombinant inbred strains - Baker, Jessica A.; Mulligan, Megan K.; Hamre, Kristin M. (Frontiers in Neuroscience, 2023)
Introduction Fetal alcohol spectrum disorders (FASD) are the leading preventable neurodevelopmental disorders and two hallmark symptoms of FASD are abnormal behavior, and cognitive and learning deficits. The severity of alcohol’s teratogenic effects on the developing brain is influenced by genetics and sex. We previously identified recombinant inbred BXD mouse strains that show differential vulnerability to ethanol-induced cell death in the developing hippocampus, a brain region important in learning and memory. The present study aimed to test the hypothesis that strains with increased vulnerability to ethanol-induced cell death in the hippocampus have concomitant deficits in multiple hippocampal-related behaviors during adolescence. Methods The current study evaluated the effects of developmental ethanol exposure on adolescent behavior in two BXD strains that show high cell death (BXD48a, BXD100), two that show low cell death (BXD60, BXD71), and the two parental strains (C57BL/6 J (B6), DBA/2 J (D2)). On postnatal day 7, male and female neonatal pups were treated with ethanol (5.0 g/kg) or saline given in two equal doses 2 h apart. Adolescent behavior was assessed across multiple behavioral paradigms including the elevated plus maze, open field, Y-maze, and T-maze. Results Our results demonstrate that the effects of developmental ethanol exposure on adolescent behavioral responses are highly dependent on strain. The low cell death strains, BXD60 and BXD71, showed minimal effect of ethanol exposure on all behavioral measures but did present sex differences. The parental –B6 and D2–strains and high cell death strains, BXD48a and BXD100, showed ethanol-induced effects on activity-related or anxiety-like behaviors. Interestingly, the high cell death strains were the only strains that showed a significant effect of postnatal ethanol exposure on hippocampal-dependent spatial learning and memory behaviors. Discussion Overall, we identified effects of ethanol exposure, strain, and/or sex on multiple behavioral measures. Interestingly, the strains that showed the most effects of postnatal ethanol exposure on adolescent behavior were the BXD strains that show high ethanol-induced cell death in the neonatal hippocampus, consistent with our hypothesis. Additionally, we found evidence for interactions among strain and sex, demonstrating that these factors have a complex effect on alcohol responses and that both are important considerations.